2018
DOI: 10.1063/1.5024009
|View full text |Cite
|
Sign up to set email alerts
|

NaCl nucleation from brine in seeded simulations: Sources of uncertainty in rate estimates

Abstract: This work reexamines seeded simulation results for NaCl nucleation from a supersaturated aqueous solution at 298.15 K and 1 bar pressure. We present a linear regression approach for analyzing seeded simulation data that provides both nucleation rates and uncertainty estimates. Our results show that rates obtained from seeded simulations rely critically on a precise driving force for the model system. The driving force vs. solute concentration curve need not exactly reproduce that of the real system, but it sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 55 publications
3
104
0
Order By: Relevance
“…34 The JC NaCl model has an equilibrium solubility of 3.7 mol/kg in SPC/E water at 298.15 K and 1 bar, confirmed by both chemical potential 35 and direct coexistence methods. 36 The nucleation rate for this system has been recently studied 12,37 using forward flux sampling methods, and from seeding simulations in conjunction with classical nucleation theory (CNT) 19,38 ; it was demonstrated that at modest supersaturations nucleation follows a classical one-step mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…34 The JC NaCl model has an equilibrium solubility of 3.7 mol/kg in SPC/E water at 298.15 K and 1 bar, confirmed by both chemical potential 35 and direct coexistence methods. 36 The nucleation rate for this system has been recently studied 12,37 using forward flux sampling methods, and from seeding simulations in conjunction with classical nucleation theory (CNT) 19,38 ; it was demonstrated that at modest supersaturations nucleation follows a classical one-step mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…A rather recent approach, named Seeding, consists in directly starting the simulation from a configuration where the nucleus of the stable phase is already formed [13][14][15][16][17]. This approach is not fully rigorous as it relies on the validity of Classical Nucleation Theory [6,18,19] and on a judicious choice for the criterion used to determine the nucleus size [20]. Despite the lack of rigor, this method has proven successful in predicting nucleation rates in crystal nucleation of hard spheres, Lennard Jones spheres, water or sodium chloride [17].…”
Section: Introductionmentioning
confidence: 99%
“…These types of simulations are used as part of the seeding method,49 which is used to predict crystal nucleation rates. The definition of the exact size of the crystal seed is one of the largest sources of uncertainty in the method 50. The test case enabled us to explore several questions regarding the behavior of the PointNet.…”
Section: Resultsmentioning
confidence: 99%